Work, wedlock and widows : comparing the lives of coloured and white women in Cape Town, 1900–1960 - Rommelspacher, Amy Fairbairn (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.